(untitled) (Journal of the College of Education for Women, 2021)
The current research focuses on examining the isohyets in a set of (3) climatic maps of Iraq. Two of these maps were published in the Iraq Climate Atlas and the third one was published in an English source about the geography of Iraq. The first map represents the period from 1923-to-1944, the second is for the period from 1961-to-1990, whereas the third represents the period from 1971-to-2000. Comparing among these three maps, it has become clear that there are noticeable changes of rain in Iraq. In the first map, which represents the decade of the twenties, thirties and early forties, Iraq was located between two Isohyet lines (127 mm) in the far south and (1270 mm) in the far north. As for the second map, which represents the sixties, seventies and eighties, Iraq became between the Isohyet lines (100 and1000 mm). This means that Iraq has lost (3) important rain lines, 1270,1134, and 1016mm. The third map, which represents the decade of seventies, eighties and nineties, displayed another important change where Iraq became between the Isohyet lines (100 and 700 mm). This means that Iraq has lost again (3) important Isohyet lines, representing by 800, 900, and1000 mm. This means that the annual rainfall in Iraq is heading towards a gradual decline. On the other hand, it has become clear that some of the equal rain lines are constantly appearing on the map of Iraq; they specifically include the following: (100, 200, 300, 400, 500, 600, and 700 mm).